Analisis Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Handphone Samsung Di Pelita Ponsel Pasir pengaraian - Hidayat., Zulfajri, Makmur, (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2017)
This study aims to identify and analyze the influence of brand image and product quality either partially or simultaneously to the Samsung Mobile Consumer purchasing decisions in Pelita phone Pasir Pengaraian. The population in this study is that people who use android phone products in Pelita Mobile Pasir Pangaraian. The research sample using judgment sampling technique with a total of 98 people. The independent variables in this study (X1) brand image, (X2) the quality of the product, the dependent variable (Y) purchasing decisions. Methods of data collection using field research and library research, field research consisted of observations, questionnaires and interviews. Analysis of data using multiple linear regression equation Y = 1.120 + 0.174 X1 + 0.274 X2. The results showed that the brand image and product quality has an influence on the purchase decision variables 70.2%. While the remaining 29.8% is explained by factors or other variables not included in the regression analysis such as price, distribution channels, quality of service and others. The conclusion of this study brand image and product quality significantly having an effect on purchasing decisions either partially or simultaneously.